Diagnostic gynecologic and obstetric pathology - Crum, Christopher P.; Nucci, Marisa R.; Howitt, Brooke E.; Granter, Scott R.; Parast, Mana M.; Boyd, Theonia K.; Haefner, Hope K.; Peter, William A. (Elsevier Inc., 2018)
Comprehensive and practice-oriented, the fully updated 3rd Edition of this easy-to-use text covers the full range of obstetric and gynecologic pathology, including information on treatment and patient management. Written largely by the pathology and clinical faculty at Harvard's Brigham and Women's Hospital, it covers the most up-to-date information available in the field, including molecular genetics and diagnostics